Contributions of Mathematicians in Mamluks State: (Historical Study) - ABDULJABBAR ABDULHAMEED, AFAF (Al-Adab Journal, 2020)
The mamluks were able to establish their State in 648 AH\ 1250 AD after they are eliminated on the AYOOBI State . During a short period , the mamluks were able to expand their State , while it included many countries as Egypt , Levant , Hujaz , Yemen and other countries . The mamluk sultans are took Cairo as a capital . After nearly two and a half centuries, the Ottomans managed to eliminate and overthrow it in 923 AH / 1517 AD. When we followed the history of this State , we found it full of political, administrative, economic and scientific achievements, as the Egyptian countries, especially after the fall of Baghdad in 656 AH / 1258 AD , the scholars came from all over the Islamic Arab country , because of the security and safety of the Egyptian countries, especially after the Abbasid Caliphate was transferred to Egypt, as well as the economic recovery of the Mamluk state, in addition the interest of the Mamluk sultans and senior statesmen in establishing schools, Biemarstanat, mosques, and offices throughout all of the Egyptian countries. They worked to provide all the requirements to ensure that it continued to perform the job it was created for. The students joined to study at the hands of the best teachers and scholars of that era such as Ibn Khaldun, Maqrizi and Suyuti and Ibn al-Nafis and many others. These conditions have helped on establishment a scientific renaissance not only limited to the religious sciences but included experimental sciences, such as medicine, pharmacy, astronomy, chemistry and physics. The mathematics is one of the mental and experimental sciences that Muslims excelled in. In this field, many scholars have emerged in various parts of the Egyptian countries such as Ibrahim bin Muhammad bin Bahadir bin Ahmed known as Ibn Ziqaqa who excelled in the field of astronomy, arithmetic, astrology and chemistry and has many books, and Ali bin Othman bin al-Hawari, who died in 833 AH / 1429 AD, who was a scholar of the statutes. Because the daily need of man and his way of life are related to some aspects of mathematics, a great role in the progress and development of this science, the urgent need to know and set the timing of prayer and other acts of worship helped to the development of mathematics and the emergence of specialists in this aspect such as Musa bin Muhammad bin Othman, who died in 805 AH / 1403 AD and he has several works it summarizes how to know the prayer times and the direction of the qiblah, and Sharaf al-Din Musa bin Muhammad al-Khalili, author of (Summarizing the Knowledge of Prayer Times and the Qiblah direction) and the book (A Message in the Astrolabe). In this research paper, we will shed light on this important science , its most prominent scholars , the most important inventions that mathematicians have reached and the relationship of this science to other sciences on the one hand and its impact on people's lives on the other hand, as well as we mentioned the most prominent books of his scientists and their scientific products.